DISTRIBUTION OF ALLELIC VARIANTS OF Wx GENES IN THE COMMON WHEAT COLLECTION MADE AT THE KRASNODAR LUKYANENKO RESEARCH INSTITUTE OF AGRICULTURE - M. V. Klimushina; N. I. Gladkih; M. G. Divashuk; L. A. Bespalova; A. V. Vasilyev; G. I. Karlov (Вавиловский журнал генетики и селекции)
Molecular marker-based identification of allelic variants of Wx genes has been performed in the collection of 99 common wheat cultivars and breeding lines developed at the Krasnodar Lukyanenko Research Institute of Agriculture.Use of two molecular markers to the Wx-А1 gene shows that cultivars ‘Starshina’ and ‘Sila’ carry null alleles of Wx-А1. Studies with four systems of molecular markers indicate that cultivars ‘Nota’ and ‘Lastochka’ possess the Wx-B1e allele. No cultivars with null-alleles of Wx-B1 have been found. Only wild-type alleles are present in the Wx-D1 locus.